RECLAIMING POWER THROUGH NATURE: ECOFEMINIST EXPLORATION OF MAHASWETADEVI’S NARRATIVES - Misra, Sarika; Bhat, K. Sripad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the intricate relationship between women and nature through the lens of ecofeminism, focusing on the works of renowned Bengali author Mahasweta Devi. Ecological feminism challenges patriarchal structures that dominate both women and the environment, while cultural ecofeminism emphasizes the innate bond between women and nature due to gender roles. Through an analysis of Devi’s short stories—The Hunt, Draupadi, and Statue—the paper examines how the protagonists’ connection with nature enables them to reclaim their identity and power within a patriarchal framework. These tribal women, deeply rooted in their ecological surroundings, draw strength and resilience from the natural world, resisting the commodification and oppression imposed by society. This paper will also underscore how both women and land have been historically treated as resources for exploitation, highlighting the need for respect and liberation. This study reaffirms the role of ecofeminism in advocating for the liberation of both women and nature from systems of dominance.